Priorities of Political Communication in Armenia’s Internal Politics - Aghayan, Narine (NAS RA)
Currently, the effective use of political communication to confront internal threats to national security is an important issue in the Republic of Armenia (RA). Among the internal threats, the author singled out the absence of a stable civil society, the non-establishment of the multi-party system, the neglect of the feedback mechanism in the state’s political communication, etc. In particular, the following are the main reasons for the weakness of the multi-party system in RA:  weak connection with voters, being active only during election periods,  unclear ideological orientation,  personnel policy, the weak structure of internal democracy and autonomy.  not sufficient representation in all provinces  non-transparency of political and financial activities,  weak control over the activity of parties.
Keywords: Political Studies; Political Philosophy